Strategi Komunikasi Antarpribadi Orang Tua Tuli dalam Pendampingan Anak di Masa Pubertas - Fefy Sheilla Putri; Palupi Palupi (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2022)
Interpersonal communication in family relationships is an important thing for everyone, including deaf parents. Communication between parents and children will affect the formation of children's character and nature. Therefore, a communication strategy is needed in providing assistance to children according to the needs and conditions of the child, especially for children entering their teens. This study was conducted with the aim of finding out how the interpersonal communication strategies of parents with deafness with their children who have normal hearing are in mentoring during puberty and the challenges they face. The theory used in this research is the theory of CMM (Coordinated Management of Meaning). This research is a qualitative descriptive study that collects data through semi-structured in-depth interviews with three deaf parents. The results of this study indicate that each informant has a strategy in providing assistance during puberty. Two informants use a catalyst strategy, and one informant uses a hanging sword strategy.